PENGARUH APLIKASI BAKTERI PELARUT FOSFAT DAN PUPUK ANORGANIK FOSFAT TERHADAP POPULASI BAKTERI PELARUT FOSFAT, P-TERSEDIA, DAN HASIL TANAMAN JAGUNG PADA ALFISOL - Gertruda Lovitna; Yulia Nuraini; Nurul Istiqomah (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2021)
Fulfilment of nutrients for plants can be maximized when fertilization, but the application of inorganic fertilizers can cause damage to the soil if the dosage is excessive. The utilization of phosphate solubilizing bacteria is an effort to increase the efficiency of phosphate fertilization that can extract phosphate from an insoluble form that becomes available. This study aimed to obtain a combination of inorganic fertilization doses (SP-36 and NPK) and the application of biological fertilizers that utilize phosphate solubilizing bacteria (PSB) to increase the population of phosphate solubilizing bacteria and P-available in the soil, as well as corn crop yields. This study used a randomized block design with nine treatments and three replications. The result showed that the application of PSB and inorganic phosphate fertilizer shows a significant effect on the population of PSB, P-available, plant height, stover dry weight, cob weight with husk and cob weight without husk, but didn’t show a significant effect on 100 seeds weight and number of plant leaves. Based on the correlation analysis, the results show a positive correlation between soil chemical properties, P-available, and corn yield.